The Pedagogy of Pop : Theoretical and Practical Strategies for Success. - Janak, Edward A. (Lexington Books, 2012)
The Pedagogy of Pop: Theoretical and Practical Strategies for Success, edited by Edward A. Janak and Denise Blum, is a tool for educators at all levels to embrace infusing popular culture into their teaching in ways that both embrace and resist contemporary thinking. Its chapters provide a range of theoretical and practical suggestions-some widely accepted, some somewhat controversial-to elicit discussion and spark creativity amongst all students.